Lead-free low-temperature sintered glass frit

By using lead-free low-temperature sintered glass frit composed of vanadium oxide, TeO2 and ZnO, the problem of difficulty in achieving low-temperature sintering and insufficient adhesion in the prior art is solved, and low-temperature sintering and excellent adhesion are achieved for sealing joints of vacuum heat-insulated multi-layer glass, OLED display panels, etc.

CN119907781APending Publication Date: 2025-04-29BASS PUBLIC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380067901.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-23
Filing Date
2023-09-14
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

In the prior art, low-temperature sintering is difficult to achieve in sealing bonding of vacuum heat-insulated multi-layer glass, OLED display panels, etc., and since the glass frit containing lead is limited by environmental problems, it is necessary to develop lead-free low-temperature sintered glass frits, and at the same time it is required to have excellent adhesion.

Method used

The lead-free low-temperature sintered glass frit consisting of vanadium oxide, TeO2 and ZnO are used. The vanadium oxide contains V2O5 and VO2. The molar ratio of V5+ ions to V4+ ions is controlled between 1.0 and 1.3 to ensure the low-temperature sintering and strong adhesion of the glass frit.

Benefits of technology

The low-temperature characteristics and excellent adhesion of lead-free low-temperature sintered glass frit are realized, and are suitable for sealing joints of vacuum heat-insulated multi-layer glass, OLED display panels, etc., avoiding the influence of high-temperature sintering on the characteristics of the joint object.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119907781A_ABST
    Figure CN119907781A_ABST
Patent Text Reader

Abstract

The present invention relates to a low-temperature sintered lead-free glass frit which can be used for sealing and bonding vacuum insulated multi-layer glass, display panels of organic light emitting diode displays (OLEDs) and the like, and other electronic components. The lead-free low-temperature sintered glass frit according to one embodiment of the present invention comprises vanadium oxide, TeO2, and ZnO, wherein the vanadium oxide comprises V2O5 and VO2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a lead-free low-temperature sintered glass frit, and more particularly to a low-temperature sintered lead-free glass frit that can be used for sealing and bonding vacuum insulation multi-layer glass, display panels of organic light emitting diode displays (OLEDs), and other electronic components. Background Art

[0002] In the bonding of vacuum insulation multilayer glass, display panels such as organic light emitting diode displays (OLEDs), and other electronic components, a sealing bonding material containing a glass composition is used. The sealing bonding material is formed in the form of a paste containing glass frit, and is applied to the bonding object by screen printing, dispensing, etc., and then sintered to seal and bond.

[0003] After being applied to the bonding object, such as insulating glass or display panel, the sealing bonding material needs to be sintered. However, if it is sintered at a high temperature, the properties of the bonding object may change. For example, if it is sintered at a temperature above 400°C when bonding tempered glass, the compressive stress of the tempered glass is weakened, resulting in a decrease in strength. Therefore, the glass frit contained in the bonding material should be able to be sintered at a low temperature.

[0004] In the past, low-temperature sintered glass frits containing Pb were widely used, but recently the use of Pb has been restricted due to environmental issues. Therefore, the development of lead-free glass compositions that do not use Pb has been actively carried out recently. For example, vanadium-based glass compositions are known as lead-free glass compositions.

[0005] On the other hand, for sealing, the glass frit is required to have low temperature characteristics and excellent adhesion. In particular, with the increase in the area of ​​heat-insulating glass and display panels, stronger adhesion than ever is required for their sealing.

[0006] In response to such a demand, the inventors of the present invention have derived a glass frit that uses a vanadium-based composition and can ensure strong adhesion characteristics. Summary of the invention

[0007] Technical issues to be solved by the invention

[0008] The present invention is intended to solve the above-mentioned problems of the prior art, and its object is to provide a lead-free low-temperature sintering glass frit that can be sintered at a low temperature.

[0009] Another object of the present invention is to provide a lead-free low-temperature sintering glass frit that can be sintered at a low temperature and has excellent adhesion properties.

[0010] Means for solving technical problems

[0011] The lead-free low-temperature sintered glass frit according to an embodiment of the present invention includes vanadium oxide, TeO2 and ZnO, and the vanadium oxide includes V2O5 and VO2.

[0012] According to an embodiment of the present invention, the molar ratio of V2O5 to VO2 may be 1.0 to 1.3.

[0013] The lead-free low temperature sintered glass frit according to an embodiment of the present invention may include 25 to 41 mol % of vanadium oxide, 15 to 40 mol % of TeO 2 , and 15 to 40 mol % of ZnO.

[0014] The lead-free low temperature sintered glass frit according to an embodiment of the present invention may further include 0.1 to 6 mol % of an alkali metal oxide, wherein the alkali metal oxide may be at least one of Li2O and Na2O.

[0015] The lead-free low-temperature sintered glass frit according to one embodiment of the present invention may contain 1 to 15 mol% of at least one of Bi2O3, B2O3, Al2O3, ZrO2, SiO2, Nb2O5, TiO2, CuO, Fe2O3, MnO2, Na2CO3, K2CO3, and BaCO3.

[0016] The lead-free low-temperature sintered glass frit according to an embodiment of the present invention may further include a ceramic filler, wherein the ceramic filler may be at least one of zirconium phosphate (ZP), zirconium-tungsten-phosphate filler (ZWP), cordierite and eucryptite.

[0017] According to an embodiment of the present invention, the glass frit may contain 5 to 20 wt % of a ceramic filler based on the entire glass frit.

[0018] The transition temperature of the lead-free low temperature sintered glass frit according to an embodiment of the present invention may be 280°C to 320°C.

[0019] The thermal expansion coefficient of the lead-free low-temperature sintered glass frit according to one embodiment of the present invention can be 65×10 -7 / ℃ to 85×10 -7 / ℃.

[0020] Effects of the Invention

[0021] According to an embodiment of the present invention, a glass frit capable of low temperature sintering can be provided by using a vanadium-based glass composition even if Pb is not included.

[0022] Furthermore, the glass frit according to an embodiment of the present invention can be sintered at a low temperature and has excellent adhesion properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a FTIR analysis chart of a sealing bonding material including a lead-free low-temperature sintered glass frit according to an embodiment of the present invention after sintering. DETAILED DESCRIPTION

[0024] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the accompanying drawings to the extent that a person having ordinary knowledge in the technical field to which the present invention belongs can easily implement them.

[0025] In order to clearly describe the present invention, the description of the parts not related to the present invention is omitted, and the same reference symbols are marked on the same components in the entire specification. It should be understood that the specific shapes, structures and characteristics recorded in the specification can be changed from one embodiment to other embodiments without departing from the concept and scope of the present invention, and the position or configuration of individual components can also be changed without departing from the concept and scope of the present invention.

[0026] Therefore, the following detailed description is not to be taken in a limiting sense, but it should be understood that the scope of the present invention includes the scope of the claims and all equivalents thereto.

[0027] The lead-free low-temperature sintered glass frit according to an embodiment of the present invention can be used for sealing and bonding vacuum insulation multi-layer glass, OLED display panels, and other electronic components.

[0028] As described above, a paste containing glass frit is applied to the joining objects such as vacuum insulation multi-layer glass and OLED display panels and then sintered to achieve joining. However, if sintering is performed at a high temperature, not only will the process cost increase, but there will also be a problem that the properties of the glass or display panel, display element, etc. that are the joining objects may change.

[0029] Therefore, in one embodiment of the present invention, a vanadium-based glass frit is used for low temperature sintering. Specifically, the lead-free low temperature sintering glass frit according to one embodiment of the present invention may include vanadium oxide, tellurium oxide and zinc oxide.

[0030] Vanadium oxide acts as a glass former and has a low melting point, so it can act as a flux that improves flow characteristics and lowers the glass transition temperature (Tg). In addition, tellurium oxide can improve the bonding strength of the glass to improve water resistance and chemical resistance and lower the glass transition temperature (Tg), and zinc oxide can improve the water resistance of the glass composition, reduce the thermal expansion coefficient, and stabilize the glass composition.

[0031] According to one embodiment of the present invention, the lead-free low temperature sintered glass frit may contain V2O5 and VO2 as vanadium oxides. That is, according to one embodiment of the present invention, the vanadium oxide of the glass frit contains V2O5 in the form of V2O5. 5+ ions, at the same time, can contain V in the form of VO2 4+ ion.

[0032] Vanadium oxides are usually 5+ However, since V2O5 has a stable glass structure, it may not be able to ensure sufficient adhesion when bonding with a bonding object (for example, a glass substrate). 4+ ions, the Si in the bonding object (for example, glass substrate) 4+ Since ions can easily diffuse into the glass frit as the bonding material, the bonding strength, that is, the adhesive force between the two can be improved as the ion diffusion distance from the bonding object to the bonding material increases.

[0033] According to one embodiment of the present invention, the vanadium oxide contained in the glass frit 5+ Ions relative to V 4+ ions in a ratio of 1.0 to 1.3. That is, based on the molar ratio, V 5+ / V 4+ is 1.0 to 1.3. If V 5+ Ions relative to V 4+ If the ratio of V is less than 1.0, the fluidity may be reduced during sintering, the adhesion may be excessively increased, cracks may be generated in the glass substrate to which it is attached, and the glass substrate may become less resistant to impact. 5+ Ions relative to V 4+ ions is greater than 1.3, the V 4+ Therefore, in one embodiment of the present invention, considering the improvement of adhesion and fluidity characteristics during sintering, V contained in the vanadium oxide of the glass frit is added. 5+ Ions relative to V 4+ The ratio of ions was set to 1.0 to 1.3.

[0034] On the other hand, according to one embodiment of the present invention, the ratio of VO2 (i.e., V 4+ The ratio of ions can be controlled by the following method.

[0035] (1) When manufacturing the glass frit composition, V is added 4+ Method for preparing ionic vanadium compounds

[0036] (2) Adding a reducing agent to a glass frit composition containing V2O5 to reduce the V2O5 5+ ions are reduced to V 4+ Ionic method

[0037] (3) Heat treating the glass frit composition containing V2O5 in a reducing atmosphere to reduce V 5+ ions are reduced to V 4+ Ionic method

[0038] According to one embodiment of the present invention, the vanadium oxide contained in the glass frit 5+ Ions relative to V 4+ The ratio of ions can be confirmed by analyzing the structure after sintering. For example, for the sealing bonding material after sintering, FTIR or XPS analysis instruments can be used to distinguish between those with V 5+ (V2O5) and V 4+ (VO2) ion valence structure, thus, it can be confirmed that V 5+ Ions relative to V 4+ The ratio of ions.

[0039] Figure 1 is a FTIR analysis chart of a sealing bonding material including a lead-free low temperature sintered glass frit according to an embodiment of the present invention after sintering. Figure 1 , by placing V 4+ The ionic structure is in the absorption band (about 925cm -1 ) and the absorbance with V 5+ The structure of ionic valence is in the absorption band (840cm -1 ) by comparing the absorbance of 5+ Ions relative to V 4+ For example, in the case of melt A, V 5+ Ions relative to V 4+ The molar ratio of ions is 1.38. In the case of frit B, V 5+ Ions relative to V 4+ The molar ratio of the ions was 1.14.

[0040] According to an embodiment of the present invention, the lead-free low temperature sintered glass frit may contain TeO 2 and ZnO as tellurium oxide and zinc oxide, respectively.

[0041] The glass frit according to an embodiment of the present invention may include about 25 to about 41 mol % of vanadium oxide and zinc oxide, about 15 to about 40 mol % of tellurium oxide, and about 15 to about 40 mol % of zinc oxide.

[0042] When the content of vanadium oxide is less than the above composition range, the glass transition temperature and softening point may increase. When the content of vanadium oxide is more than the above composition range, devitrification may occur during melting and bubbles may be generated during sintering. When the content of tellurium oxide is less than the above composition range, water resistance may be reduced, and fluidity or glass stability may be reduced. When the content of tellurium oxide is more than the above composition range, the thermal expansion coefficient may increase significantly. When the content of zinc oxide is less than the above composition range, the glass has low solubility and may be difficult to manufacture. When the content of zinc oxide is more than the above composition range, crystals are generated inside the glass and transparency may be reduced.

[0043] The lead-free low temperature sintered glass frit according to one embodiment of the present invention may further include an alkali metal oxide. As the alkali metal oxide, at least one of Li2O and Na2O may be included. According to one embodiment of the present invention, the glass frit may include about 0.1 to about 6 mol % of the alkali metal oxide.

[0044] The lead-free low temperature sintered glass frit according to an embodiment of the present invention may further include at least one of Bi2O3, B2O3, Al2O3, ZrO2, SiO2, and TiO2. According to this embodiment, the glass frit may include about 1 to about 15 mol% of at least one of the above components.

[0045] In addition, the lead-free low-temperature sintered glass frit according to an embodiment of the present invention may further include at least one of Nb2O5, CuO, Fe2O3, MnO2, Na2CO3, K2CO3, and BaCO3. When added with at least one of Bi2O3, B2O3, Al2O3, ZrO2, SiO2, and TiO2, these components may be included in an amount of about 1 to about 15 mol%.

[0046] The lead-free low-temperature sintered glass frit according to one embodiment of the present invention may further include a ceramic filler in addition to the above-mentioned components. According to one embodiment of the present invention, the glass frit may include one or more of zirconium phosphate (ZP), zirconium-tungsten-phosphate filler (ZWP), cordierite and eucryptite as the ceramic filler.

[0047] The ceramic filler has the following functions: reducing the thermal expansion coefficient of the glass frit, making the thermal expansion coefficient match that of the bonding object (e.g., glass substrate), and preventing the transfer of cracks between the bonding object (e.g., glass substrate) and the bonding material. However, if the content of the ceramic filler is too much, it is possible to reduce the adhesion with the bonding object (e.g., glass substrate), and its content needs to be limited to a certain range. For example, the glass frit according to one embodiment of the present invention can be composed of about 80 to about 95% by weight of the above-mentioned glass component and about 5 to about 20% by weight of the ceramic filler.

[0048] The lead-free low-temperature sintered glass frit according to one embodiment of the present invention having such a composition can have a 65×10 -7 / ℃ to 85×10 -7 / ℃, preferably 70×10 -7 / ℃ to 80×10 -7 / °C thermal expansion coefficient. In addition, the transition temperature of the lead-free low temperature sintered glass frit according to one embodiment of the present invention is 280°C to 320°C, and can be sintered at 370°C to 410°C.

[0049] For sealing of glass substrates, etc., the glass frit composition having the above composition can be manufactured in the form of a paste. Specifically, an organic solvent such as an alcohol solvent, a ketone solvent, an ester solvent and an organic binder such as an acrylic polymer or a cellulose polymer can be mixed to manufacture a vehicle, and a crystallized glass powder and a ceramic filler are mixed in an appropriate ratio to manufacture a paste. At this time, an inorganic pigment can also be included within the range that does not reduce the physical properties of the glass, the physical properties of the coating, etc.

[0050] Hereinafter, the characteristics of the lead-free low-temperature sintered glass frit according to one embodiment of the present invention, which have been described using specific experimental examples so far, will be specifically described.

[0051] Experimental example

[0052] Table 1 shows the compositions of glass frits according to examples and comparative examples of the present invention. The content of each component is expressed in mol%, which is a value calculated based on the content of the entire glass frit.

[0053] [Table 1]

[0054]

[0055] In the glass compositions shown in Table 1, about 10 wt% of cordierite was added as a ceramic filler. 5+ Relative to V 4+ The molar ratio (V 5+ / V 4+) as shown in Table 2.

[0056] [Table 2]

[0057]

[0058] The properties of the glass frits of the examples and comparative examples in Tables 1 and 2 are shown in Table 3. Specifically, Table 3 shows the transition temperature (T g ), thermal expansion coefficient, crystallization and adhesion properties. Here, after sintering at 400°C for 30 minutes, crystallization evaluation was carried out. In addition, adhesion evaluation was carried out through the following process.

[0059] - After applying a paste containing glass frit on the first glass substrate, the first sintering is performed

[0060] - Place the second glass substrate on the first glass substrate, arrange fillers (spacers) around the glass frit, and then perform a second sintering at the softening temperature.

[0061] -Measure the load at the moment the bonding surface is broken using a tensile tester

[0062] The evaluation value (MPa) of the adhesion evaluation was calculated as the average value of the measured values ​​by performing 10 tensile tests to measure the load at the moment when the adhesive surface was broken, and the adhesion evaluation value of 1.0 or less was judged as poor, 1.0 to 2.0 as fair, 2.0 to 3.0 as excellent, and 3.0 or more as very excellent.

[0063] [Table 3]

[0064]

[0065] Referring to Table 3, the transition temperatures (Tg) of the examples and comparative examples are all less than 310°C, showing excellent low temperature characteristics. It was confirmed that the thermal expansion coefficient in the comparative examples was slightly higher than that in the examples, but it was confirmed that it was generally at a good level. In the case of comparative example 1, crystals were generated, which is presumably due to the high content of vanadium oxide.

[0066] In the case of adhesion, it can be confirmed that there is a large difference between the embodiment and the comparative example. 5+ Relative to V 4+ In the examples where the molar ratio of V is between 1.0 and 1.3, it is confirmed that the adhesion is excellent or very excellent, and it can be confirmed that the closer it is to 1.0, the greater the adhesion. 5+ Relative to V 4+ In the comparative examples where the molar ratio of V is less than 1.0 or greater than 1.3, poor adhesion can be confirmed. 5+ Relative to V4+ In Comparative Example 4 in which the molar ratio of was less than 1.0, it was confirmed that cracks were generated.

[0067] The above experimental examples have confirmed that when the vanadium oxide in the glass frit of the lead-free system composition contains VO2, the adhesion is increased. 5+ Relative to V 4+ When the molar ratio is between 1.0 and 1.3, the adhesion is particularly excellent.

[0068] The present invention has been described above using specific matters such as specific constituent elements and limited embodiments, but the embodiments are only provided to help a more comprehensive understanding of the present invention. The present invention is not limited to these. Anyone with ordinary skills in the technical field to which the present invention belongs will understand that various modifications and variations can be made from such descriptions.

[0069] Therefore, the concept of the present invention should not be limited to the embodiments described above, and not only the claims described below, but all embodiments that are equivalent or equivalent to the claims belong to the scope of the concept of the present invention.

Claims

1. A glass frit, which is a lead-free low-temperature sintered glass frit, The glass frit comprises vanadium oxide, TeO2 and ZnO, The vanadium oxides include V2O5 and VO2.

2. The glass frit according to claim 1, wherein: Based on the molar ratio, V 5+ / V 4+ It is 1.0 to 1.

3.

3. The glass frit according to claim 1, comprising: 25 to 41 mol % vanadium oxide; 15 to 40 mol% TeO2; and 15 to 40 mol% ZnO. 4 . The glass frit according to claim 2 , further comprising 0.1 to 6 mol % of an alkali metal oxide.

5. The glass frit according to claim 4, wherein: The alkali metal oxide is at least one of Li2O and Na2O.

6. The glass frit according to claim 4, comprising 1 to 15 mol% of at least one of Bi2O3, B2O3, Al2O3, ZrO2, SiO2, Nb2O5, TiO2, CuO, Fe2O3, MnO2, Na2CO3, K2CO3, and BaCO3.

7. The glass frit according to claim 1, further comprising a ceramic filler, The ceramic filler is at least one of zirconium phosphate (ZP), zirconium-tungsten-phosphate filler (ZWP), cordierite and eucryptite.

8. The glass frit according to claim 7, wherein: The ceramic filler is contained in an amount of 5 to 20 wt % based on the entire glass frit. 9 . The glass frit according to claim 1 , having a transition temperature of 280° C. to 320° C.

10. The glass frit according to claim 1, wherein the thermal expansion coefficient is 65×10 -7 / ℃ to 85×10 -7 / ℃.